(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Abstract: Background. Supracondylar fractures are common in the pediatric age group. Delayed and neglected presentation of supracondylar fractures is frequent especially in third world countries because of various factors. There are no standard guidelines for the management of supracondylar fractures presenting late. Our study aimed at evaluating the clinical and radiological outcomes of delayed supracondylar fractures humerus, who were treated with closed calloclasis, reduction, and percutaneous fixation. Methods. A prospective cohort study was conducted from 1st July 2019 to 30th June 2020. Inclusion criteria were; Type III Gartland supracondylar fractures, and a delay in fracture presentation of equal to or more than 7 days. Exclusion criteria were; supracondylar fractures associated with neurovascular injuries, and those who required ORIF. Functional and radiological outcomes were measured using Flynn’s criteria, Baumann’s angle, and humerocaptellar angle respectively. Results. 46 patients were included in our study. The Mean age was 6.4±2.6 years, average delay in presentation was 12.13±4.4 days, with a mean postoperative follow-up duration of 14±3 months. Based on Flynn’s criteria, 71.7% of cases showed excellent grading. Conclusion. Closed osteoclasis, reduction, and percutaneous pinning and is a feasible option for delayed or neglected displaced supracondylar fractures of humerus.